A Bridge and a Large Port, Two Unpublished Projects for the Bay of Cádiz - Bambó Naya, Raimundo; Sánchez Lampreave, Ricardo (ZARCH, 2015)
Bay of Cádiz, a natural harbor of highly unique geographic profiles as is the rest of a wide estuary where the ancient Phoenician city settled, has been the scene of some of the most important episodes in the modern history of Spain. Its water level, an inner sea of changing profiles with marshes and salt lakes, has always been a strategic location relative to historical sea routes between the Mediterranean and the Atlantic, between Europe and America. Following his studies in Civil Engineering, in 1923 Eduardo Torroja began working at the Hydraulic and Civil Construction Company Hidrocivil of his teacher Eugenio Ribera. In 1927 he decided to start his own company, having started his relationship with Cádiz in 1926 calculating the foundation piles of Sancti Petri Bridge. Between 1927 and 1929, responding to two separate commissions from the mayor Ramón de Carranza, Torroja presented to the City of Cádiz the projects of a bridge that would link Puerto Real and Cádiz, thus avoiding having to go around the whole bay to access the city, and a large port that would sprawl over that bay, transforming it into a large area of port activities. None of them ended up being built, but they were the direct antecedents of the existing bridge and the current free zone that complements the current port.